2020
DOI: 10.3390/su12187537
|View full text |Cite
|
Sign up to set email alerts
|

Laundry Care Regimes: Do the Practices of Keeping Clothes Clean Have Different Environmental Impacts Based on the Fibre Content?

Abstract: Clothing maintenance is necessary for keeping clothing and textiles functional and socially acceptable, but it has environmental consequences due to the use of energy, water and chemicals. This article discusses whether clothes made of different materials are cleaned in different ways and have different environmental impacts. It fills a knowledge gap needed in environmental assessments that evaluate the impacts based on the function of a garment by giving detailed information on the use phase. The article is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 52 publications
0
25
0
10
Order By: Relevance
“…This study was one of the first of its kind to compare current consumer garment behaviour with best practices based on garment potential and recommended care practices. Wool garments have particular attributes that favour reduced environmental impacts in the garment use phase, associated with odour resistance leading to less frequent need for washing, low washing temperature requirements and suitability for air drying practices (Laitala and Klepp 2016;Laitala et al 2020). While these favourable practices are typically used for wool garments at higher rates than other fibre types, there are opportunities to further reduce environmental impacts, as shown in this analysis.…”
Section: Best Practice Garment Carementioning
confidence: 91%
See 2 more Smart Citations
“…This study was one of the first of its kind to compare current consumer garment behaviour with best practices based on garment potential and recommended care practices. Wool garments have particular attributes that favour reduced environmental impacts in the garment use phase, associated with odour resistance leading to less frequent need for washing, low washing temperature requirements and suitability for air drying practices (Laitala and Klepp 2016;Laitala et al 2020). While these favourable practices are typically used for wool garments at higher rates than other fibre types, there are opportunities to further reduce environmental impacts, as shown in this analysis.…”
Section: Best Practice Garment Carementioning
confidence: 91%
“…A survey of Dutch households (Uitdenbogerd et al 1998) showed that those who commonly aired their garments conducted 22.5% fewer washes than the average household. More recent studies on laundering practices found that wool garments were worn more days between cleaning cycles than garments made of other fibres (Laitala et al 2018(Laitala et al , 2020, indicating that airing of wool garments is practised by many consumers. However, large variations exist in how many times a wool garment is worn before it is washed; responses varied from 1 to more than 30 wears, and in some cases, garments had not been washed since purchase (Wiedemann et al 2020).…”
Section: Inventory Data and Description Of Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, it is questionable whether and how producers and consumers can influence this life cycle phase, especially explicitly. Even though some studies demonstrate that fibre and garment type can influence consumer behaviour, they also show that laundry practices are highly dependent on cultural and country specific effects (habit of hand washing, quality of washing machines, use of tumble dryers) [61,62]. They are further linked to garment use, social auditing, cultural norms, garment aesthetics, life stage, and household arrangements [63].…”
Section: Focus Points and Gaps In The Textile Ecolabelingmentioning
confidence: 99%
“…For example, shared laundries (e.g., communal laundry rooms within a multi-family building, or a commercial coinoperated facility) are often used in the Philippines (Retamal and Schandl 2018), Japan and Thailand (Moon 2020) and Finland (Miilunpalo and Raisanen 2019). A recent study by Laitala et al (2020) also found that the use of shared washing machines varied between 6 and 13% among consumers in China, Germany, Japan, UK, and the USA. For Sweden, shared laundries were introduced during the 1920s and have been the norm throughout the nation since the 1950s (Lund 2009).…”
Section: Introductionmentioning
confidence: 99%